Failure Analysis of a Deep Pit on the Inner Wall of Water Wall Tube in a Power Plant. Issue 1 (1st January 2023) - Zhang, Yiwen; Fang, Lulu; Tao, Kangning; Chu, Xi; Dai, Zhen
Abstract: A deep pit on the inner wall of a water wall tube of a 600MW boiler was found at the extension end of the front of the furnace during an overhaul after 200 thousand hours of operation. To investigate the causes of the failure, various techniques including macroscopic inspection, chemical composition analysis, microstructural analysis, mechanical performance testing, scanning electron microscope (SEM) observation and energy dispersive spectroscopy (EDS) analysis were carried out. The results of investigations showed that the chemical composition of the as-received tube conformed with SA-178 Grade C and the mechanical properties were qualified. EDS analysis revealed that the main elements of the deposit on the surface of the pit were iron and oxygen, along with phosphorus, potassium and aluminium, which were identified with the constitutes of the under deposit corrosion products. Based on the results, the cause of the failure is under deposit corrosion. Possible measures to combat the corrosion were proposed.